STRATEGI PENGEMBANGAN AGRIBISNIS TANAMAN HIAS PALEM WEREGU (Rhapis excelsa) DI KOTA PEKANBARU PROVINSI RIAU - Andika Pratama Elza; Syaiful '; Novia ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Rhapis plant is one of the plantation which has the potential to be developed in Pekanbaru city because it is one of the high producers area of rhapis plant in Riau Province. The purpose of this research: 1) Determine agribusiness system of rhapis plant in Pekanbaru City, 2) Formulate agribusiness development strategy of rhapis plants in Pekanbaru City. The method used in this study is a survey method by using purposive sampling. Total populations of rhapis farmers in Pekanbaru is 9 rhapis farmers. 2  farmers were sampled according to the criteria of the study. Farmers who are still active in the cultivation and marketing of rhapis plants. The results of the study shows that agribusiness of rhapis plants have a marketing problem is the low price specified by exporters and transportation cost by farmers from Pekanbaru to the port of Tanjung Priok, Jakarta. Agribusiness development priority strategy of rhapis plant is (1). A partnership between farmers and shopkeepers rhapis plants (2). Reducing dependence on exports of raphis (3). Increasing the role of the government in controlling price of rhapis that farmers profit price and bargaining position of farmer (4). Increasing sales of rhapis export scale with government (5). Expanding land rhapis nursery for seedling availability rhapis for  farmers.   Keywords ; Agribusiness of Rhapis, Development Strategy, Agribusiness development,   SWOT analysis